Cost-benefit analysis and emission reduction of energy efficient lighting / Gao Wei - Gao , Wei (2018)
With the development of society and the growth of population, the usage of global power is increasing day by day. Of all power consumers, lighting accounts for the largest share of power consumption in the commercial and residential sectors. Lighting accounts for about 20% to 30% of global electricity consumption. As a result, lighting systems have great potential for energy savings. Thus, the main objective of this research project is to design the proper retrofit scenario and analyses the potential power savings, payback periods and potential environmental benefits. In this study, new energy-efficient LED lamps were used to retrofit existing lighting systems. At the beginning of 2018, all lighting systems were replaced, and the power consumption, payback period, life cycle cost and emissions were calculated. The 100% retrofit of existing lighting systems with LED lamps can save about 44.7% of energy consumption per year. The results of the life cycle analysis suggest that about two years later, the selected buildings will generate net saving and feasible for the investment. Using data access and calculations to predict the percentage of electricity consumption and fuel generation fuels in Malaysia, after 100% modifications, total emissions can be reduced by approximately 2,622 ton of CO2, 11,197 kg of SO2, 6,336.4 kg of NOx and 1,904 kg of CO. Hence, the use of energy-efficient lighting systems will save a lot of energy and costs, while also reducing emissions.